Locusts of the year 2000 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
The fact that there have been no mass invasions of desert or migratory locusts for twenty years or so does not mean that the threat is over. When the rains returned to the Sahelian region of Africa last year there were several localised invasions....